Environmental management and the reshaping and respacing of livelihoods in sub-Saharan Africa: a short commentary on recent trends and conceptual ideas. Issue 1 (2nd January 2019) - Krüger, Fred; Samimi, Cyrus
Abstract : In recent years, many regions in sub-Saharan Africa have experienced growing contestations of existing livelihood practices and massive environmental change. This has been accompanied by what has sometimes been described as a 'respacing' of Africa, i.e. an increasing blurriness of the nation state and social relationships becoming more and more interconnected on the local to global scales, rendering conventional concepts of space and territory obsolete. In this introductory essay, we briefly discuss notions of this 'respacing' process, highlight its validity but also its ambiguity, and thus lay the ground for the ensuing compilation of papers on social, environmental, and spatial change in sub-Saharan Africa.